Colonization of Malassezia Species on Healthy Skin of Preschool Children - Evelyn González de Morán; María Lucía Delmonte; Robertiz Sandra; Priscila Fernández; Luzmila Mesa; Sofía Rodríguez de Valero (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2011)
Malassezia yeast forms part of the normal skin on man and other vertebrates. Recent descriptions of new species have stimulated interest in their study in diverse countries; it is important to conduct further research to collect epidemiological data about the species in tropical countries such as Venezuela. This study was made on healthy skins of preschool-age children (2 to 7 years). Samples were taken from different areas of the body, inoculated into a modified medium of Dixon and Sabouraud Agar and incubated at 32°C. Species identification was made following the code described by Guého and collaborators. In the population of children, three species were isolated: M furfur, M. globosa and M. slooffiae. The predominant species was M. furfur with 76.2% in all ages studied, followed byMglobosa, 16.7%, and M. slooffiae, 7.1%. In relation to anatomical locations, M. furfur predominated on the back (31.2%), followed by the auricle (outer ear) and chest (21.9%), respectively.Mglobosa was most frequently isolated from the scalp (71.4%) and M. slooffiae was observed on the back (66.7%) and the auricle (33.3%). According to the statistical tests applied, there were no significant differences between the evaluated groups. It is important to continue this research with other age groups, to establish the prevalent species in this region and evaluate their pathogenic potential.